Influence Of Incentives On Work Spirit And Performance Of Village Collectors In Receipt Of Pbb-P2 - Munandar; Sopiah (International Journal of Educational Research & Social Sciences, 2021)
The research objective is to analyze the Influence of Incentives on Work Spirit and Performance of Village Collectors in Accepting PBB-P2 in Rokan Hulu Regency. Sources of data are village collector respondents in 16 sub-districts in Rokan Hulu Regency. The sample was set at 48. The data analysis techniques were descriptive analysis, validity and reliability testing, and path analysis using IBM's SPSS 19. The research results show (1) Incentives (X) directly affect work morale (Y1). (2) Incentives (X) directly affect the performance of village collectors (Y2). and (3) directly work enthusiasm (Y1) has a direct effect on the performance of village collectors (Y2) in Rokan Hulu Regency, and indirectly Incentives (X) have a significant effect on Collector Performance (Y2) through Work Spirit (Y1) village collectors in Rokan Hulu Regency.